1989
DOI: 10.1007/bf00042630
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine mutagenesis is associated with substantial heritable variation in cotton

Abstract: Seedlings of the cotton cultivar Sicot 1 were treated with either 1%, 2% or 5% colchicine in lanolin which was topically applied to the apical meristem four days after emergence . Of 293 1%-treated seedlings 64 survived to produce fertile C, shoots which gave rise to 84 C2 single boll families . C2 and C3 generations were examined in field experiments for morphological variants and for a number of quantitative characters (yield components and fibre quality) . No morphological mutants were seen but considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 14 publications
1
36
0
1
Order By: Relevance
“…In the APM treatment at 20 mg⋅l -1 , however, the survival rate of the carnation explants was relatively high. It has been reported that colchicine caused sideeffects, such as sterility, abnormal growth and morphology, chromosome losses or rearrangements and gene mutation in many species (Luckett 1989, Wan et al 1989. In contrast, APM seemed to be a more efficient chromosome-doubling agent than colchicine and could be considered to be a suitable alternative to colchicine (Sri Ramulu et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the APM treatment at 20 mg⋅l -1 , however, the survival rate of the carnation explants was relatively high. It has been reported that colchicine caused sideeffects, such as sterility, abnormal growth and morphology, chromosome losses or rearrangements and gene mutation in many species (Luckett 1989, Wan et al 1989. In contrast, APM seemed to be a more efficient chromosome-doubling agent than colchicine and could be considered to be a suitable alternative to colchicine (Sri Ramulu et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Following the discovery by Blakeslee and Avery in 1937, colchicine has been successfully used to induce polyploids in various plant species such as barley (Gilbert and Patterson 1965); azalea (Pryor and Frazier 1968); Phalaenopsis (Griesbach 1981); Iris (Yabuya 1985); cotton (Luckett 1989); cranberry (Dermen and Henry 1994); cyclamen (Ishizaka andUematsu 1994, Takamura andMiyajima 1996) and Brachiaria brizantha (Pinheiro et al 2000). In carnation, tetraploids were artificially induced by the application of a drop of a colchicine solution on to the shoot tips (Yamaguchi and Kakei 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, induced polyploid breeding provides a wider germplasm base for breeding programs (Luckett, 1989;Aranada et al, 1997;Osborn et al, 2003;Shao et al, 2003;Thao et al, 2003;Comai, 2005;Omidbaigi et al, 2010). By preventing microtubule assembly and arresting spindle formation during mitosis, colchicine is conventionally and successfully used to induce chromosome doubling in the development of tetraploids (Takamura and Miyajima, 1996;Pinheiro et al, 2000;Nguyen et al, 2003;Petersen et al, 2003;Shao et al, 2003;Liu et al, 2007;Urwin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In various studies on induced polyploidy, the regeneration of mixoploid plants has been reported as a major problem, since the genetic stability of these partial polyploids is unknown. Another aspect to be considered, and usually neglected, is the delayed effect of colchicine (LUCKETT, 1989), the main polyploidization agent used in grasses, which can lead to chromosomal losses and rearrangements with strong impacts on fertility (LUCKETT, 1989).…”
Section: Introductionmentioning
confidence: 99%